Discussion of the published article by I. Ecsedi, A. Baksa (2017) Free axial vibration of nanorods with elastic medium interaction based on nonlocal elasticity and Rayleigh model Mech. Res. Commun. 86 1-4 - Guven, Ugur (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This paper discusses the accuracy of the fundamental governing equation based on Rayleigh rod theory and the nonlocal integral model, for the longitudinal vibration derived in [6]. This discussion shows that; when shear presence is neglected, the nonlocal Rayleigh-Bishop wave solution existing in the literature cannot be reduced to the present nonlocal wave solution presented by these authors. Since the nonlocal Love wave solution must be recovered from the nonlocal Rayleigh-Bishop wave solution, hence, this case is an unexpected result.(C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Longitudinal wave; Nonlocal love wave solution; Nonlocal Rayleigh-Bishop wave solution; Hamilton principle; PROPAGATION; WAVES; Mechanics